Correlation between the well-being of children and caregivers - Suchitporn Lersilp (2018)
© 2018 Lersilp and Putthinoi. Background: Well-being relates to the quality of life of people; such as the knowledge and behavior of caregivers regarding the health and care of their children, personal welfare and benefits for the environment, which are indicators of health planning for children and caregivers in the community. Objective: The purpose of this study was to explore the personal and environmental well-being of children and caregivers and examine the correlation between their well-being in a northern-Thai suburban community. Methods: The study comprised of two phases, which developed and examined the content validity and reliability of the questionnaires used on the well-being of children and caregivers, and interviewed participants by using the questionnaires. The participants included thirty Thai children aged 3-6 years and twenty-nine caregivers. Results: The results indicated that 8 behavioral items (38.10%) of well-being were presented by the children, and 13 (61.90%) not, while 9 behavioral items (28.13%) of well-being were presented by the caregivers, and 23 (71.87%) not. The Pearson’s coefficient of correlation of well-being and personal well-being between the children and caregivers had a significant relationship (r = 0.423, p = 0.040 and r = 0.383, p =.022, respectively). However, it did not correlate significantly in terms of environmental well-being. Conclusion: There was a significant correlation between the well-being of children and their caregivers, particularly in personal well-being. This study provided an understanding that can be used as fundamental information that enables healthcare teams to perceive the well-being of caregivers and their children, which relates to achieving healthy behavior.